Effects of positive education approach on academic boredom, intrinsic motivation, positive emotions and thought-action repertoire among private college students in Shaanxi Province, China - Jie, Zheng (2022)
Academic boredom can be best described as a negative and deactivating academicrelated activity emotion, which is frequently reported by Chinese college students. High levels of academic boredom are associated with multiple learning factors such as intrinsic motivation. To date, however, scarce intervention studies have addressed this issue, especially among Chinese college students. More importantly, most of them adopted the deficit-based approaches which make students with high levels of academic boredom feel being labelled as problematic, and others who may not have high levels of academic boredom feel temporarily neglected, imposing an adverse impact on their mental health. Additionally, those intervention studies only aimed to reduce academic boredom, while few studies examined the effects of interventions on both reducing academic boredom and increasing positive constructs like intrinsic motivation and positive emotions. Given the limitations, further studies on academic boredom are more imperative. The purpose of this study was to investigate the effects of the positive education approach (PEA) based on China’s “6+2” positive education model on learning-related boredom (LRB), class-related boredom (CRB), intrinsic motivation (IM), positive emotions (PE), and thought-action repertoire (TAR) among Chinese private college students as compared to the traditional education approach (TEA). This study is an experimental study using a quasi-experimental non-equivalent pre-test posttest control group design due to its naturally existing groups (intact classes). The participants obtained through cluster random sampling and fishbowl technique were four intact classes students, totaling of 173 undergraduate freshmen (139 females and 34 males) ranging in age from 17 to 23 (M=19.18, SD=.1) years from China. After that, random assignment was used to assign two intact classes as the control group and two intact classes as the experimental group. The experimental group received 13 sessions of positive education interventions based on China’s “6+2” positive education model using the activity teaching pattern, which is defined as the PEA, while the control group received 13 sessions of college student mental health education course according to official documents using the teacher-centred lecturing style, which is defined as the TEA. All participants were asked to complete the assessments two times: pre-test (one week before the intervention) and post-test (one week after the intervention). The results showed that: PEA was effective in reducing LRB and CRB, and increasing IM. The mean score in LRB for post-test (M=22.00, SD=7.59) was significantly lower than that for pre-test (M=31.12, SD= 9.08) (p .01). The same results were found for CRB, where the mean score in CRB for post-test (M=21.14, SD=7.24) was significantly lower than that for pre-test (M=29.98, SD=9.20) (p .01). In addition, the mean score in IM for post-test (M=62.52, SD=12.07) was significantly higher than that for pre-test (M=53.58, SD=13.80) (p .01). The profile plot indicated that there were increases in the mean score for PE from pre-test (M=26.57, SD=5.68) to post-test (M=28.43, SD=6.29) and TAR from pre-test (M=8.13, SD=5.20) to post-test (M=9.27, SD=5.70) that were not statistically significant; the TEA was not effective in reducing students’ LRB, CRB and increasing IM, PE, and TAR (p .01). There were no statistically significant differences in the mean scores of LRB, CRB, IM, PE, and TAR from pre-test to post-test (p .01); the PEA was much better than the TEA in reducing students’ academic boredom (LRB, CRB) and improving their wellbeing (PE, TAR) as well as academic success (IM) (p .01). An examination of the mean scores indicated a significantly lower level of LRB in the experimental group (M=22.00, SD=7.59) than in the control group (M=31.11, SD=8.28) (p .01); a significantly lower level of CRB in the experimental group (M=21.14, SD=7.24) than in the control group (M=31.17, SD=9.40) (p .01); a significantly higher level of IM in the experimental group (M=62.52, SD=12.07) than in the control group (M=54.30, SD=14.35) (p .01); a significantly higher level of PE in the experimental group (M=28.43, SD=6.29) than in the control group (M=25.51, SD=5.41) (p .01); a significantly higher level of TAR in the experimental group (M=9.27, SD=5.70) than in the control group (M=5.48, SD=4.01) (p .01). Thus, the PEA can both reduce academic boredom and increase intrinsic motivation in China. Positive emotions and thought-action repertoire could also be improved but the significance level did not occur. This study provided empirical evidence that PEA is one of the effective interventions in addressing both academic boredom and motivational issues in education that are increasing due to various development happening in the students’ surroundings.